2008
DOI: 10.1111/j.1365-2699.2008.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

The antiquity of Madagascar’s grasslands and the rise of C4 grassy biomes

Abstract: Aim Grasslands and savannas, which make up > 75% of Madagascar's land area, have long been viewed as anthropogenically derived after people settled on the island c. 2 ka. We investigated this hypothesis and an alternative -that the grasslands are an insular example of the post-Miocene spread of C 4 grassy biomes world-wide.Location Madagascar, southern Africa, East Africa.Methods We compared the number of C 4 grass genera in Madagascar with that in southern and south-central African floras. If the grasslands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
195
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(203 citation statements)
references
References 55 publications
7
195
0
1
Order By: Relevance
“…Bond et al [76] explored the question of whether Madagascan grasslands are ancient or, as has long been argued, products of deforestation in the 2000-4500 years since people settled the island. They argued that if the grasslands were secondary they would be expected to have low diversity, few if any open-habitat specialists, and low species turnover across environmental gradients.…”
Section: (A) Diversity and Endemismmentioning
confidence: 99%
“…Bond et al [76] explored the question of whether Madagascan grasslands are ancient or, as has long been argued, products of deforestation in the 2000-4500 years since people settled the island. They argued that if the grasslands were secondary they would be expected to have low diversity, few if any open-habitat specialists, and low species turnover across environmental gradients.…”
Section: (A) Diversity and Endemismmentioning
confidence: 99%
“…This is particularly true of assumptions related to burning regimes, particularly in grassland ecosystems (see, for example, Foster and Motzkin, 2003;Maxwell, 2004). A number of recent studies have indicated that in regions that climatically should be able to support trees (e.g., S. Africa and Madagascar), there is a tendency to assume that all grasslands are a consequence of previous anthropogenic activity (Bond et al, 2008). By the classification of grasslands as "anthropogenic" they often acquire the label of a "degraded" landscape and therefore are of little conservation priority.…”
Section: Which Ecological Processes Are Important For Maintaining Tarmentioning
confidence: 99%
“…In many parts of the world there remains considerable controversy as to whether savannas are the result of anthropogenic fire-activity or arise independent of human fireuse (Willis et al 2008;Bowman and Haberle 2010;McWethy et al 2010), with some authors arguing that plant and animal species diversity can be used as evidence against human agency (Bond et al 2008;Foreman 2016). In the case of Tasmanian sedgelands the diverse, and in some cases endemic, vascular (Corbett and Balmer 2007;Lawrence et al 2007) and non-vascular (Kantvilas 2007) flora and vertebrate (Driessen 2007) and invertebrate (Driessen et al 2014) fauna points to an ancient ecosystem that preceded human colonisation in the late-Pleistocene.…”
Section: Simulation Model Experimentsmentioning
confidence: 99%